Exercise training affects hemodynamics and exercise capacity in cases of heart failure with preserved ejection fraction: a non-randomized controlled trial in individuals aged 65–80 years - Sugita, Yousuke; Ito, Katsuhiko; Yoshioka, Yui; Kudo, Ayano; Arakawa, Sota; Sakai, Satoshi (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Exercise training is an established intervention method for improving exercise capacity and survival rates in patients with heart failure with preserved ejection fraction (HFpEF). However, most reports have focused on European and American patients, with limited data regarding the effects of exercise training on cardiac function, hemodynamics, and exercise capacity in East Asian patients. This study investigated the effects of exercise training on cardiac function, hemodynamics, and exercise capacity in Japanese patients aged 65-80 years with HFpEF. Methods: This single-center, open-label, non-randomized, controlled trial prospectively enrolled 99 outpatients. Eligibility criteria for HFpEF patients were an HFA score ≥5 in addition to clinical symptoms of heart failure and left ventricular diastolic dysfunction.Exercise training in the intervention group consisted of aerobic exercise and strength training thrice weekly for 5 months. Patients in the control group continued the usual treatment for 5 months. Resting cardiac function was evaluated using echocardiography. Peak oxygen uptake (peakVO2), ventilatory equivalent (VE) vs. carbon dioxide output (VCO2) slope, peak cardiac output index, and arteriovenous oxygen difference were calculated using cardiopulmonary exercise testing combined with impedance cardiography. Results: After 5 months of exercise training, remarkable interactions were observed, with peakVO2 as the primary outcome.Additionally, significant interactions were observed between hemodynamic indices and some echocardiographic parameters. The mean percentage change in peakVO2 from baseline was 8.3% in the intervention group. Fifteen study participants (30.1%) in the intervention group achieved a clinically meaningful change of 3.0 mL/min/kg (10% improvement) in peakVO2 from baseline. The group with 3.0 mL/min/kg or 10% improvement in peakVO2 from baseline had a considerably lower prevalence of diabetes mellitus and VE vs. VCO2 slope and considerably higher left atrial-global longitudinal strain values than the group without any notable improvements. Conclusions: Although exercise training can help improve exercise intolerance in Japanese patients aged 65-80 years with HFpEF, its benefits are limited. Our results suggest that HFpEF, complicated by diabetes mellitus and decreased ventilatory efficiency during exercise, may require reconsideration of intervention strategies. This trial was registered with the University Hospital Medical Information Network, a trial registry in Japan (registration number: UMIN000045474).